Comparing the Effect of Vitamin E and N-Acetylcysteine on Prevention of Contrast-Induced Nephropathy in Diabetic Patients under Coronary Angiography - Pishgahi, Mehdi; Niroomand, Mahtab; Taziki, Omolbanin; Shahi, Sepideh; Karimi Toudeshki, Kimia; Mirzaei Pirloo, Mina (Archives of Men's Health, 2021)
Introduction: Considering the incidence of contrast induced nephropathy (CIN) as well as its complications and costs, prevention and reducing the risk of CIN is an essential issue. The present study aimed to evaluate the efficacy of vitamin E and N-acetylcysteine (NAC) on the prevention of CIN in diabetic patients undergoing coronary angiography. Materials and Methods: 360 patients with diabetes who required angiography, including patients with stable angina susceptible to acute myocardial infarction and patients with acute coronary syndrome were included and randomized into three groups . Group 1 received serum therapy (Normal Saline) plus NAC and placebo of vitamin E, group 2 received serum therapy plus vitamin E and placebo of NAC, and group 3 only received serum therapy with two placebos of NAC and vitamin E. The groups were compared considering CIN after angiography. Results: A total of 93 patients were studied in group 1, 94 in group 2, and 113 in group 3. CIN occurred in 4 patients (4.3%), 4 patients (4.3%), and 8 patients (7.1%) in groups 1, 2, and 3, respectively (P=0.58). There was a significant difference in mean difference of creatinine levels before and after study in groups 1 and 2 (both P<0.001). In the subgroup of patients with chronic kidney disease, NAC significantly reduced CIN (P=0.03). Conclusion: The results suggested efficacy of both interventions, considering reduction of mean Serum creatinine ( Scr) after the study, while lack of significant difference in the incidence of CIN could be because of the low number of CIN in our study. The second important finding of this study, probably the reduced risk of CIN in diabetic patients with chronic kidney disease receiving NAC, recommends the use of NAC for prevention of CIN, especially in this subgroup of patients undergoing angiography.